Implementasi business intelligence dashboard untuk visualisasi data pasien posbindu ptm binaan uptd puskesmas kecamatan - Dini Nurmalasari; Nurzikriah Nurzikriah (Politeknik Caltex Riau, 2021)
Posbindu PTM (integrated non-communicable disease fostered post) is a form of community participation in early detection, monitoring and early follow-up of PTM risk factors independently and continuously. The target of this program is aimed at all healthy and at-risk communities aged 15 years and over. This PTM Posbindu activity is held once a month. For Rokan IV Koto sub-district there are 10 Posbindu PTMs. After conducting the survey, the management of Puskesmas Rokan IV Koto has managed patient data using excel as a source of annual performance reporting. However, management Puskesmas Rokan IV Koto had difficulty getting information from patient data in accordance with the management's wishes. What the management of Puskesmas Rokan IV Koto wants is to know the distribution pattern of PTM, patients and patients at risk of PTM. The design of this system uses tools including: Framework CodeIgniter, PHP as a programming language and MySQL as a DBMS. This system is tested using black box testing and user acceptance test (UAT). Based on the user acceptance test (UAT) that has been carried out, it shows that 88% of the system that has been built has been accepted by the user and black box testing shows that the function has been running 100%. The benefit of this business intelligence system is that it is able to assist the head of the puskesmas in making decisions. Keywords: Puskesmas Rokan IV Koto, Patient Data, Business Intelligence, MySQL, PHP